The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.21071/az.v63i241.573
|View full text |Cite
|
Sign up to set email alerts
|

Características da carcaça e da carne de cordeiros Corriedale manejados em duas alturas de milheto

Abstract: O objetivo deste estudo foi avaliar características de qualidade da carcaça e da carne de cordeiros Corriedale manejados em duas alturas de pastejo em milheto. A terminação dos cordeiros foi feita em pastagem anual de verão, milheto cultivar comum (Pennisetum americanum (L.) Leeke.). Os tratamentos consistiram de duas alturas de pastejo, 20 e 40 cm. Os animais foram abatidos baseando-se na condição corporal ao atingirem o índice entre 2 e 3 (1 a 5). Foram realizadas avaliações quantitativas e qualitativas da c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…In our study, suckling lambs presented average values of carcass compactness index higher than to those found for weaned lambs, with values of 0.25 and 0.24 kg cm −1 for suckling lambs on pasture and in confinement, respectively, and 0.21 and 0.19 kg cm −1 for weaned lambs fed roughage and concentrate, respectively. These results are in accordance with the average values of carcass compactness index found by Lira et al 2017and Lemes et al (2014), who found values of 0.22 and 0.19 kg cm −1 , respectively.…”
Section: Variablesupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, suckling lambs presented average values of carcass compactness index higher than to those found for weaned lambs, with values of 0.25 and 0.24 kg cm −1 for suckling lambs on pasture and in confinement, respectively, and 0.21 and 0.19 kg cm −1 for weaned lambs fed roughage and concentrate, respectively. These results are in accordance with the average values of carcass compactness index found by Lira et al 2017and Lemes et al (2014), who found values of 0.22 and 0.19 kg cm −1 , respectively.…”
Section: Variablesupporting
confidence: 92%
“…Studies on carcass quality have been increasing in Brazil, as well as on factors that affect its quality (LEMES et al, 2014). However, few studies have been conducted to compare the different lamb finishing systems (POLI et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation